Business Ethics Perspectives: Faculty Plagiarism and Fraud - Elliott, Teressa L.; Marquis, Linda M.; Neal, Catherine S. (2013)
Faculty plagiarism and fraud are widely documented occurrences but little analysis has been conducted. This article addresses the question of why faculty plagiarism and fraud occurs and suggests approaches on how to develop an environment where faculty misconduct is socially inappropriate. The authors review relevant literature, primarily in business ethics and student cheating, developing action steps that could be applied to higher education. Based upon research in these areas, the authors posit some actions that would be appropriate in higher education and suggest topics for continued study.
Keywords: Faculty fraud; Faculty plagiarism; Organizational Ethics; Faculty misconduct; Ethics; Business Ethics; Academic misconduct